ANALISIS PENGARUH KUALITAS LABA DAN NILAI PERUSAHAAN TERHADAP AUDIT DELAY ABNORMAL - Anandika Ibna Pratama; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the influence of earnings quality and firm value on abnormal audit delay. This study also examines abnormal audit delay as moderating variable, that is used its influence on firm value.The Population of this study is all listed firms in Bursa Efek Indonesia in year 2010 – 2014. The sampling method in this study is stratified random sampling. By doing sampling dan processing data, the final amounts of the sample are 250. This study uses multiple regression analysis technique to examine the hypotheses.The results of this study show that the influence between earnings quality and abnormal audit delay has a bad or negative significant influence. Earning report delay has positively significant influenced on abnormal audit delay. Abnormal audit delay decreases the relationship between relative excess value on profitability.